Editing Asiatic and the burden of carrying Mohammad A. Quayum’s legacy forward - Hasan, Md. Mahmudul (IIUM Press, International Islamic University Malaysia, 2020)
Students of literature mostly focus on creative writers and their lives and works. Literary critics and editors like Mohammad A. Quayum who evaluate and promote creative writers and writings rarely receive adequate attention. Literary critics contribute immeasurably to our understanding of various literary traditions by shedding light on contextual aspects that influence writers and their literary productions. They draw attention to various features of literature which may otherwise remain unappreciated, unnoticed, or uninterpreted. His prominence as a first-class, celebrated scholar of literature of global stature is a cause of pride, especially for Asiatic, for IIUM and his other affiliations, and for his homeland, Bangladesh. The burden of carrying his legacy of Asiatic forward is most humbling for me.